Gender roles and traits in stress and health - Mayor, Eric (Frontiers in Psychology, 2015)
Women have a life-expectancy advantage over men, but a marked disadvantage with regards to morbidity. This is known as the female-male health-survival paradox in disciplines such as medicine, medical sociology and epidemiology. Individual differences in physical and mental health are further notably explained by the degree of stress individuals endure, with women being more affected by stressors than men. Here, we briefly examine the literature on women’s disadvantage in health and stress. Beyond biological considerations, we follow with socio-cognitive explanations of gender differences in health and stress. We show that gender roles and traits (masculinity in particular) explain part of the gender differences in stress, notably cognitive appraisal and coping. Stress in turn degrades health. Implications are discussed. In conclusion, traditional socialization is advantageous for men in terms of health.